Ripartitella brunnea, a new species from subtropical China - Zhang, Ming; Li, Tai-Hui; Wei, Tie-Zheng; Liang, Xi-Shen; Liu, Zhu-Xiang (Phytotaxa, 2019)
Ripartitella brunnea, collected from southern China, is described, illustrated and discussed as a new species based on unique morphological characteristics and molecular data. Ripartitella brunnea is characterized by its light brown to violet brown pileus covered with dark brown squamules, slightly involute margin appendiculate with white to yellowish white veil remnant; white and crowded lamellae; fleeting annulus; echinulate basidiospores 4.5–6 × 3.5–4 µm in size and lageniform pleurocystidia often covered with yellowish crystals at apex. Phylogenetic analyses based on the combined datasets ITS and LSU sequences confirmed that R. brunnea is a new member of Ripartitella.